Novel furoquinolinones from an Indonesian Plant, Lunasia amara. Issue 20 (14th May 2020) - Yamashita, Masaki; Saito, Yohei; Rahim, Abdul; Fukuyoshi, Shuichi; Miyake, Katsunori; Goto, Masuo; Nakagawa-Goto, Kyoko
Graphical abstract: Highlights: Two new furanoquinolones, racemic 3-oxolunacrine (1 ) and 2, 3-dehydrolunacrine (2 ), were isolated from Lunasia amara . Pure ( S )- and ( R )-isomers of 1 were separated by chiral column chromatography. The possibility that racemic 1 occurs naturally was discussed based on a proposed biosynthetic pathway. Abstract: Two new furanoquinolones, 3-oxolunacrine (1 ) and 2, 3-dehydrolunacrine (2 ), and 22 known quinolones (3–24 ) were isolated from the methanol extract of the bark of Lunasia amara . The chemical structures of the newly isolated compounds were elucidated from HRMS and various NMR spectroscopic data. Pure ( S )- and ( R )-isomers of 1, which was obtained as a racemate, were separated by chiral column chromatography. The possibility that racemic 1 occurs naturally was discussed based on a proposed biosynthetic pathway. Selected isolated quinoline alkaloids were evaluated for antiproliferative activities against five human tumor cell lines, including a multidrug-resistant cell line overexpressing p-glycoprotein.